THU0019 BLyS Expression in Synovial Fluids from Rheumatoid Arthritis Patients. (23rd January 2014) - Mas, L.; Saurit, V.; Cortiñas, E.; Colazo, M.; Alvarellos, A.; Alvarellos, T.
Abstract : Background: BLyS is a novel TNF family ligand, mainly secreted by myeloid cellsandsynovial fibroblasts that exerts profound effects on B cells leading to their maturation and increased survival. Local expression of BLyS in inflamed joints from Rheumatoid Arthritis (RA) patients may contribute to the development and progression of disease. Objectives: We evaluated local gene expression of BLyS in RA patients with disease activity. Methods: Synovial fluids and Peripherical Blood (PB) were obtained from RA patients and were classified in two groups, Group I: RA evaluated by DAS 28 score as high disease activity (n=10, 7F/3M, age: 56, 3 ± 20, 9, range: 17-84) and Group II: Osteoarthritis (OA, n=18, 13F/5M, age: 70, 5 ± 6, 6, range: 58-86). Levels of BLyS expression were evaluated using Quantitative Real Time PCR (QPCR). All amplifications were carried out in duplicate and threshold cycle (Ct ) scores were averaged for calculations of relative expression values. The Ct scores were normalized against Ct scores by subtracting the corresponding β2Microglobuline (β2M) control, or ΔCt=Ct, gene - Ct, B2M . To test for differential gene expression between groups, a two sample t-test was performed to compare the ΔCt in the two groups. Results: BLyS gene expression is shown in Table 1 . Conclusions: Increased BLyS expression in active RA SF can be linked to B cell activation and proliferation in RA synovium. References: Tan SM et al. Local Production of B lymphocyte Stimulator Protein and APRIL in Arthritic Joints of Patients with Inflammatory Arthritis. Arthritis and Rheumatism. 48 (4):982-992 (2003). Kreuzaler M et al. Soluble BAFF Levles inversely correlate with Peripherical B cell numbers and the expression of BAFF receptors. J Immunol. 188: 497-503 (2012). Disclosure of Interest: None Declared